1993
DOI: 10.1088/0022-3727/26/9/013
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of electron swarms in SF6in uniform E*B fields

Abstract: Reports electron swarm parameters in SF6 in uniform E*B fields employing a Monte Carlo simulation technique. The parameters studied are transverse and perpendicular drift velocities, magnetic deflection angle, collision frequency, mean energy and effective ionization coefficients for 30 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 10 publications
(6 reference statements)
0
14
0
Order By: Relevance
“…The generalisation of Tonks' theorem (i.e., the drift speed in the E × B direction is equal to the drift speed in an electricfield-only situation, with E = E e [38,39]) to nonconservative processes follows directly. The utility of the effective electric field concept has been justified by Dincer [6] using Monte Carlo simulation in the case of electron swarms in SF 6 . We note, however, that in the case of spatial inhomogeneity, no such simple relation as (23) exists, as is shown in the following section.…”
Section: Definition Of Transport Coefficientsmentioning
confidence: 99%
See 1 more Smart Citation
“…The generalisation of Tonks' theorem (i.e., the drift speed in the E × B direction is equal to the drift speed in an electricfield-only situation, with E = E e [38,39]) to nonconservative processes follows directly. The utility of the effective electric field concept has been justified by Dincer [6] using Monte Carlo simulation in the case of electron swarms in SF 6 . We note, however, that in the case of spatial inhomogeneity, no such simple relation as (23) exists, as is shown in the following section.…”
Section: Definition Of Transport Coefficientsmentioning
confidence: 99%
“…Ness [16] gave the first comprehensive theoretical prescription applicable to nonconservative collisions and there have been subsequent investigations of nonconservative effects for crossed fields in both model and real gases [18,19]. Dincer [6] investigated electron transport in SF 6 in the crossed field configuration, where both attachment and ionization processes are operative in spatially homogeneous condition using Monte Carlo simulation. Petrovic et al [23, 40a, 40b] have studied nonconservative collision effects on electron transport parameters in spatially uniform conditions in an orthogonal field configuration using momentum transfer theory [15].…”
Section: Introductionmentioning
confidence: 99%
“…The deviation is attributed rather to the fact that the collision frequency of each electron is actually energy-dependent although the macroscopic collision frequency which is the integrated value over the swarm seems constant. Dincer (1993) showed that the ionization coeécient in SF 6 is a function of the eãective reduced electric åeld (E=N ) eã = (E=N ) cos í , where í is the Hall angle. A similar situation is found also in F 2 .…”
Section: Fmentioning
confidence: 99%
“…Dincer and Gokmen (1992) measured electrical breakdown properties of SF 6 , and subsequently Dincer (1993) and Milsom (1993) calculated electron transport coeécients in SF 6 employing a Monte Carlo method. Shimura and Makabe (1993) analyzed the electron velocity distribution in Ar using a Boltzmann equation technique.…”
Section: Introductionmentioning
confidence: 99%
“…Because the model for the electron swarm and the Monte-Carlo technique used for calculating the critical fields have been described by the authors elsewhere [11,15,17,18], only a brief description of the method is in order. The technique is based on a free-flighttime approach in which the three-body collisions and Coulomb interactions are neglected based on the assumption that the gas is weakly ionized.…”
Section: Simulation Methods and The Modeling Of The Electron Swarmmentioning
confidence: 99%